Dukungan Sosial dan Strategi Menghadapi Stigma Negatif Anak Berkebutuhan Khusus Dalam Pendidikan - Raden Safira Ayunian Widhiati; Elly Malihah; Sardin Sardin (Universitas Pendidikan Mandalika, 2022)
This study aims to describe social support and strategies to deal with the negative stigma of children with special needs in education. This study used a qualitative approach with a case study method. The technique used in determining the subject of this study was accidental sampling, namely parents, school committees and teachers. Data collection techniques through observation, interviews and documentation. Data analysis in this study was used the data reduction, data display and conclusion drawing or verification. Based on the results of the study, there were several children with special needs who experienced negative stigma either from speech, ridicule, or being touched by others. As for social support, especially acceptance from parents and other family members, it will provide 'energy' and confidence in children with special needs to make more efforts to learn and try new things related to life skills and in the end they can achieve. Social support provided to children with special needs includes emotional support, information, or materials for assistive devices. Social support is very influential on children with special needs in making these children do not feel different from normal children. The strategy in dealing with stigma is by attending educational classes with three pathways, namely formal education, informal education and non-formal education.